The Level of Society Knowledge about Preventive Stunting Supplement and DAGUSIBU at Jatisela Village - Nadea Murpratami; Eka Wuri Handayani; Arnika Dwi Asti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Stunting in Indonesia still becomes a critical health matter in the society. Knowledge regarding folic acid, iron, vitamin A, and anthelmintic is so essential to decrease the amount of stunting. The utilization of the supplement must be correct and appropriate by applying DaGuSiBu (Get, Use, Save, Throw) principle in order to not result any negative impacts for its user, thus a counselling related to this issue is very required to increase the public’s knowledge. This research intends to compare the knowledge level of the society before and after preventive stunting supplement and DaGuSiBu counselling. This research utilizes a door-to-door method with One group pretest-posttest design. The sample of this research is people of Jatisela village as many as 70 people. Data collection utilizes pretest and posttest sheet. The data obtained is analyzed using the Wilcoxon test. The result of the Wilcoxon test at pretest and postest demonstrates that there is a knowledge improvement on the respondents after a counselling has been given with score p-value=0,000 (<0,05). There are 37 from 70 respondents whose score is increased after the counselling has been done. The level of knowledge is divided based on good, sufficient, and deficient category. The percentage of knowledge level at good category increases from 1,0% to 52,8%, sufficient category from 6,14% to 41,4%, and deficient category from 37,3% to 5,8%. From thesse data, it can be concluded that a counselling could increase the knowledge of Jatisela village’s society significantly.